2017
DOI: 10.1159/000481262
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Evaluation of the Fellow Eye of Patients with Retinal Angiomatous Proliferation

Abstract: Introduction: We conducted a multimodal, cross-sectional evaluation. Methods: Eyes were divided into 4 study groups: controls, early/intermediate age-related macular degeneration (AMD), fellow eyes of retinal angiomatous proliferation (RAP), and RAP eyes. Patients were evaluated with spectral-domain optical coherence tomography (OCT), enhanced depth imaging-OCT, and OCT angiography (OCTA). OCTA images were processed to generate maps of the vessel density and perfusion density of the superficial and deep retina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The presence of small retinal hemorrhages, macular soft drusen, and RPD is highly predictive of MNV3, and especially intraretinal hemorrhages are a distinguishing feature from typical CNV ( Yannuzzi et al, 2001 ; Kim et al, 2014 ; Tsai et al, 2017 ). RPE atrophy, GA, and focal hyperpigmentation are common features in the fellow eyes of MNV3 ( Martins et al, 2018 ). RPD and a large area of soft drusen are risk factors for bilateral MNV3 (Miki Sawa et al, 2014 ; Marques et al, 2015 ; Chang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of small retinal hemorrhages, macular soft drusen, and RPD is highly predictive of MNV3, and especially intraretinal hemorrhages are a distinguishing feature from typical CNV ( Yannuzzi et al, 2001 ; Kim et al, 2014 ; Tsai et al, 2017 ). RPE atrophy, GA, and focal hyperpigmentation are common features in the fellow eyes of MNV3 ( Martins et al, 2018 ). RPD and a large area of soft drusen are risk factors for bilateral MNV3 (Miki Sawa et al, 2014 ; Marques et al, 2015 ; Chang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Martins et al [ 6 ] also noticed a significantly lower vascular perfusion of the DCP in patients with RAP.…”
Section: Discussionmentioning
confidence: 95%
“…In the last years, several studies performed to understand the pathogenesis of type 3 MNV, supported the intraretinal origin, highlighted early stages' features of type 3 NV, and demonstrated the presence of reticular pseudodrusen as a risk factor to the development of type 3 MNV [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 95%
“…Several studies have reported fellow eye characteristics of AMD with type 3 neovascularization, suggesting they include atrophy of the RPE, the presence of reticular pseudodrusen, increased numbers of drusen, hyper-reflective foci, and reduced retinal and choroidal blood flow [6,33,39,40]. In this study, we classified RPE features concisely to assess the status of eyes with certain retina, GCIPL, and choroidal thickness values intuitively.…”
Section: Discussionmentioning
confidence: 99%